Assessment of the REPLACE study composite endpoint in riociguat‐treated patients in the PATENT study. (1st December 2020) - Simonneau, Gérald; Ghofrani, Hossein‐Ardeschir; Corris, Paul A.; Rosenkranz, Stephan; Grünig, Ekkehard; White, Jim; McLaughlin, Vallerie V.; Langleben, David; Meier, Christian; Busse, Dennis; Kleinjung, Frank; Benza, Raymond L.
Abstract : The goal of treatment in patients with pulmonary arterial hypertension is to achieve a low risk status, indicating a favorable long‐term outcome. The REPLACE study investigated the efficacy of switching to riociguat in patients with pulmonary arterial hypertension and an insufficient response to phosphodiesterase‐5 inhibitors. In this post hoc analysis, we applied the REPLACE composite endpoint of clinical improvement to the placebo‐controlled PATENT‐1 study of riociguat in pulmonary arterial hypertension and its long‐term extension, PATENT‐2. Clinical improvement was defined as ≥2 of the following in patients who completed the study without clinical worsening: ≥10% or ≥30 m improvement in 6‐minute walking distance; World Health Organization functional class I or II; ≥30% decrease in N ‐terminal prohormone of brain natriuretic peptide. At PATENT‐1 Week 12, patients treated with riociguat were more likely to achieve the composite endpoint vs. placebo ( P  < 0.0001), with similar results in pretreated ( P  = 0.0189) and treatment‐naïve ( P  < 0.0001) patients. Achievement of the composite endpoint at Week 12 was associated with a 45% reduction in relative risk of death and a 19% reduction in relative risk of clinical worsening in PATENT‐2. Overall, these data suggest that use of the REPLACE composite endpoint in patients with pulmonary arterial hypertension is a valid assessment of response to treatment.